Interobserver Reproducibility of Dna-Image-Cytometry in Ascus or Higher Cervical Cytology - Vu Quoc Huy Nguyen; Hans Jürgen Grote; Natalia Pomjanski; Kristiane Knops; Alfred Böcking (Cellular Oncology)
In the present study, the aim has been to investigate the interobserver reproducibility of DNA‐image‐cytometry (DNA‐ICM) applied to routine Pap smears classified as Atypical Squamous Cells of Undetermined Significance (ASCUS) or higher lesions (ASCUS+). 202 Pap smears diagnosed as ASCUS or higher were included in the study. After cytological assessment, smears underwent restaining according to Feulgen. First measurements were performed as routine workup. The second measurements were blinded to the result of the first and consecutively performed. DNA‐ICM met the consensus statements of the European Society of Analytical Cellular Pathology (ESACP). Interobserver agreement was assessed by calculating Kappa statistics. The diagnosis of DNA‐aneuploidy in the first measurements was confirmed in all cases. Second measurement detected 12 additional cases with aneuploidy. Nine out of these cases were classified as aneuploidy by detection of 9c Exceeding Events (9cEE). In three cases stemline‐aneuploidy was disclosed. The overall proportion of observed agreement was 94.1%, κ=0.87, 95% CI=0.74–0.99. Our study shows a good interobserver reproducibility of DNA‐ICM performed on cervical smears with ASCUS or higher lesions. DNA‐ICM thus represents a highly reproducible diagnostic procedure.